The Art Expression of the Prisoners 'Paintings in Class IIA Narcotic Correctional Institution, Yogyakarta - Pitaloka, Mayang; Iswidayati, Sri; Triyanto, Triyanto (Universitas Negeri Semarang, 2018)
Expressing art is one of people's aesthetic needs, no exception the prisoners of class II A narcotics penal institution, Yogyakartawho fulfill their aesthetic need by doing painting activity. This is quite interesting because in the life full of freedom limitation, the citizens of the institution are still able to enliven the activity to express their aesthetic needs through painting in the prison environment. Therefore, the aim of this research is to analyse the influence of the penal institution environment toward the art expressions of the institution assisted citizens' paintings, their painting process, and the characteristics of their paintings seen in the perspectives of visual elements and principles, and in the perspective of psychoanalysis towards the painting themes. The research conducted applies qualitative and anthropology interdisciplinary approaches, aesthetics, and art psychology. The research design used is case studies. The data of the research are collected by conducting observation technique, interview, and documentation study. Then triangulation technique is used to check the validity of the data collected. Data analysis technique is conducted through reduction, presentation and verification. The results of the analysis show that, first, the environment of the penal institution has influence on the psychological stress of the prisoners which gives impact on their painting ideas, themes, and visuals; second, their creation process in various limitations do not stop their productivity in painting; and third, the visual characteristics of the prisoners’ paintings have their own uniqueness which can be seen through the perspectives of visual elements and principles related to the Id, Ego, and Superego drives in psychology which produce two categories of painting themes, i.e. political and personal themes. Both themes indicate the influences of environment, stressor, and the prisoners’ life background factors. Painting activity can be a fulfillment to the need of expressing aesthetics of every prisoner in Class IIA Narcotic Correctional Institution, Yogyakarta.